Disease Classification by Human Fingernail Colour Image Processing - Azman, Khaleef Afdal; Wan Kairuddin, Wan Nur Hafsha (Evolution in Electrical and Electronic Engineering, 2022)
This project focuses on image recognition using four different fingernail colour analysis which is yellow, white, pale and pink as to identify the type of disease where changes in nail colour is a symptom of a variety of disorders that primarily affect the nails. Image processing techniques are applied by converting the image into a digital form to extract features of a fingernail for disease classification as to classify disease such as liver disease from a white nail, lung disease from a yellow nail, anaemia disease from the pale nail and compare them with a healthy pink nail. Each fingernail image will be uploaded into the GUI first to go through the image pre-processing, binary image, and segmentation techniques. These techniques isolate the type of colour that is detected and give what the type of colour is. Once the colour has been identified, the type of disease detected will be displayed in the GUI system. The red green blue (RGB) value is used as a fingernail characteristic for fingernail colour analysis and disease detection. In this project, it is used the RGB value of the input image to classify the diseases, but it may include other features of the fingernail, such as the pattern of the fingernail to classify the diseases.